Título Padrão - Pfeiffer, Dietmar K. (Revista Dialectus - Revista de Filosofia, 2020)
Quantification is no longer a practice of natural science only but has become part of human sciences and everyday life as well. As a direct measurement, which fits the axiomatic of the representational theory of measurement, is mostly infeasible in the social sciences, indicators are used and frequently aggregated to indexes. The index scores can be used to construct a ranking of the units (HDI, PISA). Measurement level and meaning of the data remain often unknown (pseudo-metrical scaling). Furthermore many variables in the field of education are not quantifiable. In the course of globalization and international competition, an indicator system for educational quality measurement (PISA, TIMMS) and goal achievement (Education for All, Millenium Development Goals, Sustainable Development Goals), was established and exerts an increasing impact on national educational systems.The main concerns of indicator-based steering are its methodological limitations and the transformation from a descriptive information base to a normative control system.